Illicit money: financing terrorism in the twenty-first century - Davis, Jessica (Lynne Rienner Publishers, 2021)
Terrorists need money ... to recruit and train people, to buy weapons, to maintain safe houses, to carry out attacks. Which raises the question: how do they procure and protect funds to finance their operations? In Illicit Money, Jessica Davis thoroughly answers that question. Davis explores the full spectrum of terrorist finance, drawing on extensive case studies to dissect how individuals, cells, and organizations raise and manage, as well as hide, funds. In her concluding chapters, she considers both opportunities and challenges related to countering these illicit activities.